Old Land in Muarajambi Temple - Mirna Dwirastina; Sondang M. Siregar; Hendra (Criksetra: Jurnal Pendidikan Sejarah, 2022)
The Muarajambi temple area is a Buddhist temple complex dating from the 10th century AD. This area is located in a fluvial landscape and on a flat and dry land surface. This study aims to determine a) the stratification of rock formations, b) the types of soil and c) the relationship between the temple soil and religious scriptures in the construction of the temple. The method used is the method of explaining theory through data, with data collection, processing and interpretation. Collecting data through literature and field observations with photo documentation, collecting 22 soil samples. Furthermore, data processing was carried out for making stratigraphic maps of rock formations, sending 22 soil samples for texture analysis to laboratories and laboratories to determine soil texture and analyzing the relationship between soil types in Muarajambi enshrinement area with religious books. The results showed that Muarajambi temple area was in the stratigraphy of the Muara Enim rock formation, with clay content so that the footprint could be seen as hard/stable, the soil type was ultisol and referred to the Ksatria soil in the Manasarasilpasastra religious book.